STUDIES ON THE MALE REPRODUCTIVE ORGANS IN THE SUBFAMILY EREMNINAE - PAJNI, H. R.; SHOBHA, AMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Male reproductive system has been studied in 13 species under a genera of subfamily Eremninae. The number of testes has been found to be 1 pair in genera Doliophron Mshil., Indophytoscaphus Pajni & Sidhu and Platynycterius Mshil and 2 pairs in genera Heteroptochus Fst., Phytoscaphus Schoenh, Hemerus Mshl., Peltotrachelus Mshl. and Amblyrrhinus Schoenh.